2018
DOI: 10.1136/archdischild-2018-315549
|View full text |Cite
|
Sign up to set email alerts
|

Screening for coeliac disease in 1624 mainly asymptomatic children with type 1 diabetes: is genotyping for coeliac-specific human leucocyte antigen the right approach?

Abstract: ObjectivesTo investigate the frequency of coeliac disease (CD)-specific human leucocyte antigen (HLA) genotypes in paediatric patients with type 1 diabetes (T1D), who are known to have a higher prevalence of CD than the general population, and to evaluate whether HLA genotyping is a suitable first-line screening method for CD.Study designThe study was a multicentre observational analysis of patients with T1D aged <20 years of whom a subgroup had undergone HLA genotyping. Patient data were retrieved from the Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Therefore, testing for HLA-DQ2/DQ8 as the first-line screening for CD in diabetic children is insufficient. This finding in accordance with Mitchell27 and Binder28 who reported that HLA genotyping is not indicated as a firstline for CD screening in DM1. Moreover, this may improperly prevent the patients with less common CD permissive HLA alleles from future screening 26…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, testing for HLA-DQ2/DQ8 as the first-line screening for CD in diabetic children is insufficient. This finding in accordance with Mitchell27 and Binder28 who reported that HLA genotyping is not indicated as a firstline for CD screening in DM1. Moreover, this may improperly prevent the patients with less common CD permissive HLA alleles from future screening 26…”
Section: Discussionsupporting
confidence: 91%
“…“No‐Celiac Disease” (no‐CD) was defined as being CD specific antibody negative, having had no duodenal biopsy and no documented CD diagnosis. Autoantibodies considered in the database were endomysial autoantibodies (EMA), transglutaminase autoantibodies (anti‐tTG) and gliadin autoantibodies, as previously described . T1D patients with biopsy results corresponding to Marsh‐classification ≥2 and positive CD specific auto‐antibodies prior to biopsy were classified as patients with biopsy‐proven celiac disease (CD) .…”
Section: Methodsmentioning
confidence: 99%
“…The literature data show that, depending on the population, negative screening rates are different and for most European countries remain at a very low level-a few/twelve percent [2,6,11,13,14]. Moreover, the low usefulness of HLA genotyping in another contexts has been recently described in a study based on the data from the international DPV registry (Diabetes Prospective Follow-up; including >75000 patients with T1D, with HLA testing in >1600 children) [15]. The authors analyzed the history of CD diagnoses and observed that even in HLA-negative patients, both positive markers of CD (49 out of 234 patients) and the CD itself confirmed with biopsy (7/234) were relatively frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Strictly following ESPGHAN recommendations, i.e., performing HLA as a negative first-line screening that excludes the need for further observation, would not be the right procedure for such patients. Furthermore, analyses of the costs of performing HLA genotyping, as a preliminary risk verification, showed that such proceeding is not justified [6,15]. Therefore, the latest ISPAD 2018 recommendations conclude that genotyping is not a currently recommended method of screening for CD in patients with T1D [3].…”
Section: Discussionmentioning
confidence: 99%